Structural determination of aspericins A-C, new furan and pyran derivates from the marine-derived fungus Rhizopus sp. 2-PDA-61, by 1D and 2D NMR spectroscopy - Wang, Fazuo (Magnetic resonance in chemistry : MRC, 2010)
Copyright 2009 John Wiley & Sons, Ltd.